Affective music processing: Challenges - Phon-Amnuaisuk, Somnuk (Springer Berlin Heidelberg, 2005)
Our states of mind keep on changing all the time. How do we determine a mapping between our states of mind and music stimulus? In this report, we discuss, from a bird’s eye view, the meanings and effects of music which are impressed upon us. We review related literature in musical meanings and computational model, and finally we discuss the impression while listening to the fourth movement of the Pastoral. We point out challenges and suggest plausible computational approches to the affective music computing.